1975
DOI: 10.1002/app.1975.070191025
|View full text |Cite
|
Sign up to set email alerts
|

New method of determining contact angle between monofilament and liquid

Abstract: SynopsisThis paper describes a method to obtain contact angle by observing the shapf of a liquid drop attached to a monofilament. The relations between contact angle and the dimensions of drops are theoretically obtained. Thus, it is possible to calculate the contact angle if drop shape is measured. Through use of this method, the contact angles of epoxy resin on various kinds of monofilamente were measured. It was found that this method has practical utility for measurement of the contact angle between liquid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
0
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(64 citation statements)
references
References 3 publications
3
60
0
1
Order By: Relevance
“…This shows that the contact angle of a microdroplet on a fiber is a material constant, independent of the geometrical aspect ratio and equal to that on a flat surface. This confirms the choice of constant contact angle in previous works [5], [6]. Now let us further consider the Euler-Lagrange equation (9).…”
Section: Problem Formulation and Solution Proceduressupporting
confidence: 84%
See 2 more Smart Citations
“…This shows that the contact angle of a microdroplet on a fiber is a material constant, independent of the geometrical aspect ratio and equal to that on a flat surface. This confirms the choice of constant contact angle in previous works [5], [6]. Now let us further consider the Euler-Lagrange equation (9).…”
Section: Problem Formulation and Solution Proceduressupporting
confidence: 84%
“…The wetting shape of a microdroplet on a fiber does not appear as a partial sphere as that on a flat surface. Within the framework of Laplace's formula of surface tension and Young's equation of wetting angle, Yamaki and Katayama [5] first studied the shape of a microdroplet on a fiber by solving the governing equation numerically. Carroll [6] considered this problem through an analytic approach, and he found that the droplet shape could be expressed as the combination of Legendre's elliptical functions of the first and second kinds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The contact angle of fibres was measured by the numerical method, using as a base of logarithm Laplace's equation, converted by Yamaki and Katayama [41] into a differential form that takes into account the axial-symmetrical shape of the drop profile and the cylindrical fibre shape. Two liquids were used: α-bromonaphthalene and glycerine.…”
Section: Contact Anglementioning
confidence: 99%
“…The change in the surface of PET fibres after modification with esterases from hydrophobic to hydrophilic resulted also in the improvement in the resistance to soiling and oil-soil release [19] as well as dyeability with disperse dyes [1,8,32,41].…”
Section: Introductionmentioning
confidence: 99%